Field trialling of a pulse airtightness tester in a range of UK homes. Issue 1 (2nd January 2019) - Cooper, Edward; Zheng, Xiaofeng; Wood, Christopher; Gillot, Mark; Tetlow, David; Riffat, Saffa; De Simon, Lia
ABSTRACT: A low pressure 'quasi-steady' pulse technique for determining the airtightness of buildings has been developed and compared with the standard blower-door technique for field-testing a range of UK homes. The reported low pressure air pulse unit for determining the airtightness of buildings, through several development stages related to optimising the algorithm, pressure reference and system construction, has been trialled under various testing and environmental conditions to assess its repeatability and accuracy. The houses, representative of the UK housing stock, mostly have high levels of air leakage; resulting in poor energy performance and imbalanced indoor environments. The results of the pulse technique are also compared with the standard blower-door technique. The comparison indicates that the pulse technique is reliable for determining building leakage at low pressure. Repeatability of consecutive tests in identical conditions is found to be within ±5% of the mean, and within ±8% when tested under different environment conditions. It has also been shown that the correct tank/valve combination is necessary to achieve the required quasi-steady flow. Tests for accuracy using the addition of known openings have been conducted and shown that uncertainties are hard to eliminate for a clean comparison when testing conditions are not controlled.